Neuroimaging in acute infection-triggered encephalopathy syndromes - Takanashi, Jun-ichi; Uetani, Hiroyuki (Frontiers in Neuroscience, 2023)
Acute encephalopathy associated with infectious diseases occurs frequently in Japanese children (400–700 children/year) and is the most common in infants aged 0–3 years. Acute encephalopathy is classified into several clinicoradiological syndromes; acute encephalopathy with biphasic seizures and late reduced diffusion (AESD) is the most common subtype, followed by clinically mild encephalitis/encephalopathy with a reversible splenial lesion (MERS) and acute necrotizing encephalopathy (ANE). Neuroimaging, especially magnetic resonance imaging (MRI), is useful for the diagnosis, assessment of treatment efficacy, and evaluation of the pathophysiology of encephalopathy syndromes. MRI findings essential for diagnosis include delayed subcortical reduced diffusion (bright tree appearance) for AESD, reversible splenial lesions with homogeneously reduced diffusion for MERS, and symmetric hemorrhagic thalamic lesions for ANE. We reviewed several MRI techniques that have been applied in recent years, including diffusion-weighted imaging for the characterization of cerebral edema, arterial spin labeling for evaluating cerebral perfusion, and magnetic resonance spectroscopy for evaluating metabolic abnormality.